2020
DOI: 10.1108/jmd-01-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership style on organizational citizenship behavior: does leaders' emotional intelligence play a moderating role?

Abstract: PurposeThe study investigates the effect of autocratic, democratic and transformational leadership styles on employees' organizational citizenship behavior (OCB). The study further examines the moderating role of leaders' emotional intelligence between leadership styles and OCB.Design/methodology/approachQuestionnaires were used to collect data from 618 small and medium-sized enterprises' (SMEs) employees in Ghana. For this study, both simple random and convenient sampling were adopted in selecting respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 93 publications
7
46
0
11
Order By: Relevance
“…Banwo and Du (2019) pointed out that perceived control from leadership can promote employee pro-environmental behaviors by establishing social norms within SMEs. Abdullahi et al (2020) confirmed that SME employees' organizational citizenship behavior (OCB) is inspired by democratic and transformational leadership, which both refer to supportive leadership styles and entail the followings: authorization and creativity, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 74%
See 1 more Smart Citation
“…Banwo and Du (2019) pointed out that perceived control from leadership can promote employee pro-environmental behaviors by establishing social norms within SMEs. Abdullahi et al (2020) confirmed that SME employees' organizational citizenship behavior (OCB) is inspired by democratic and transformational leadership, which both refer to supportive leadership styles and entail the followings: authorization and creativity, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 74%
“…Researchers have applied conservation of resource theory to analyze the influences of different types of SME leadership on personal behavior outcomes (Özer and Tınaztepe, 2014;Bojadziev et al, 2019;Cortes and Herrmann, 2020). To unpack the underlying mechanisms, scholars, furthermore, have focused on the mediating roles of individual psychological mechanisms, such as perception (Abdullahi et al, 2020) as well as consciousness (Banagou et al, 2021). In this paper, we select job insecurity and territorial consciousness as two aspects of individual mental characteristics to explain the underlying mechanisms of the "black box" between SME differential leadership and knowledge hiding.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thereby, this article's results provide that the actual accomplishment of the FRLD theory is in establishing an approach and framework that allows for a complete examination of leadership development. However, the theory does not guarantee success as mitigating factors include culture, race, communication, and elements of the exalted transformational leadership (Abdullahi, Anarfo, & Anyigba, 2020). Nevertheless, the approach does provide ample opportunity for the full range of leadership development.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Oguz's (2010) research shows a positive correlation between teachers' organizational citizenship behaviors and transformational forms of leadership, where the leader teacher views the teacher as part of the organization. The research of Abdullahi, Anarfo, & Anyigba, (2020), argues that the implementation of a democratic transformative leadership has a positive effect on the organizational behavior of teachers' citizenship, as opposed to the results of the implementation of an authoritarian leadership model. Lian, & Tui's (2012) research argues that the implementation of transformational leadership can be positively related to state organizational citizenship behavior, while on the contrary results have resulted in the implementation of transactional leadership.…”
Section: Discussionmentioning
confidence: 99%